The Multidimensional Paradigm of Indonesian Historiography and Its Teaching Efforts in the Context of History Learning in Indonesia - Ananto Wibowo, Bayu; Djono (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
The multidimensional paradigm of Indonesian historiography is an approach in the preparation of Indonesian history considering various dimensions involving cultural, social, political, economic and environmental aspects. This paradigm has great relevance in the context of history learning in Indonesia as it helps learners understand their rich and diverse history. This approach helps overcome biases in history. Indonesia's history over the centuries has been influenced by various ethnic, religious and cultural groups. By considering the multidimensional dimension, learning history can avoid narrow views that only reflect the viewpoint of one particular group or interest. Learners are thus encouraged to become critical thinkers and can also develop a deeper understanding of their own history. Especially in History, this paradigm supports historiography with an Indonesian-centric style.